Penggunaan Model Pembelajaran LASTIK dalam Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Kemampuan Mengemukakan Pendapat, dan Hasil Belajar Siswa - Nurlaila Dwe Khairiyati; Aslamiah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Pancasila Education at the elementary school level should ideally equip students with relevant 21st-century skills, including critical thinking and the ability to express opinions. However, reality indicates that the learning process is still dominated by conventional methods, rendering students passive and unaccustomed to voicing their thoughts during instruction. This study aims to describe and analyze in depth the implementation of the LASTIK learning model—a combination of Problem-Based Learning and Talking Stick—to enhance students' 21st-century skills. Examining this combined model is crucial to addressing the educational gaps observed in the fourth grade of SDN Kuin Utara 1 Banjarmasin. Left unaddressed without appropriate intervention, these issues will not only result in low academic achievement but also hinder students' ability to solve contextual problems. This study employed a Classroom Action Research (CAR) design, utilizing observation, written tests, and documentation as data collection techniques. The findings demonstrated that the development of these five aspects was not isolated but closely interconnected. Optimally executed teacher activities enhanced student engagement, which ultimately contributed to the cultivation of critical thinking skills and an improved ability to express opinions. Consequently, these results led to more optimal learning outcomes. This indicates that the LASTIK model is proven effective in Pancasila Education to comprehensively advance students' knowledge, attitudes, and skills.